Fertilización química del híbrido de maiz (Zea mays L.) DEKALB 7088 en la zona de Ventanas. - Mesías Mesías, Wilson Rolando (2015)
This experiment was conducted in the Villa Rosita property of Mrs. Rosa Santana Complex located in bananas, the area's Windows, Los Rios Province and whose theme was the following "chemical fertilization of hybrid corn (Zea mays L.) in the 7088 Dekalb Window "This research lasted 120 days. Aim of this investigation determined the following objectives: to evaluate the chemical fertilization of hybrid corn (Zea mays L.) 7088 Dekalb area Windows, determine the effect of chemical fertilizer on the agronomic performance of maize and dose assessment more efficient chemical fertilizer on the agronomic performance of maize crop. Design of randomized complete block (RCBD) was used and the Tukey test was used at 0.05% level and the coefficient of variation is expressed in percentage. The variables height of ear insertion, plant height, weight of hundred grains, number of grains per ear, ear length, ear diameter, number of harvested plants and grain yield per hectare were analyzed. Treatment 7 Compound of nitrogen dose of 220 kg of urea ha-1 + 210 kg of complete fertilizer, presented the best average height of insertion of ear, plant height, weight of hundred grains, number of grains per ear, ear length, ear diameter, number of harvested plants and grain yield per hectare.